Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Komitmen Organisasi dan Kinerja Pegawai Universtas Nahdlatul Ulama Surakarta - Kristiani, Endah (Graduasi: Jurnal Bisnis & Ekonomi, 2015)
This study aims are to determine the effect of leadership, organizational culture on theÂ  performanceÂ  ofÂ  employeesÂ  inÂ  theÂ  UnivercityÂ  ofÂ  NahdlatulÂ  UlamaÂ  SurakartaÂ  with commitment as an intervening variable. Â Data analysis techniques used path analysisÂ  (path analysis ),Â  whichÂ  will be tested with theÂ  t test, F test and test R2 Â , Correlations, direct effect and indirect effect and total effect. TheÂ  techniqueÂ  ofÂ  collectingÂ  dataÂ  usingÂ  questionnaires,Â  theÂ  sampleÂ  areÂ  employes at the Univercity of Nahdlatul Ulama Surakarta as many as 30 respondents. T- testÂ  resultÂ  showedÂ  leadershipÂ  hasÂ  positiveÂ  andÂ  significantÂ  impactÂ  onÂ  employee commitment,Â  organizationalÂ  cultureÂ  hasÂ  positiveÂ Â  andÂ  insignificantÂ Â Â  effectÂ  onÂ  employee commitment.Â  AsÂ  forÂ  variableÂ  leadershipÂ Â Â  andÂ  commitmentÂ  haveÂ  aÂ  positiveÂ  and significantÂ  effectÂ  onÂ  theÂ  performance,Â  organizationalÂ  cultureÂ  hasÂ  positiveÂ  and insignificantÂ  effectÂ  onÂ  theÂ  performanceÂ  ofÂ  employeesÂ  inÂ  theÂ  UnivercityÂ  ofÂ  Nahdlatul Ulama Surakarta. F test showed simultaneously leadership, organizational culture and commitmentâsÂ  organizationsÂ  hasÂ  significantÂ  positiveÂ  effectÂ  onÂ  theÂ  performanceÂ  of employees in the Univercity of Nahdlatul Ulama Surakarta. The value of the coefficient ofÂ  determinasiÂ  RÂ  squareÂ  ofÂ  0,9413orÂ  94,13%.Â  ThisÂ  meansÂ  thatÂ  theÂ  employeeâs performanceÂ  isÂ  explainedÂ  byÂ  theÂ  variableÂ  leadership,Â  organizationalÂ  cultureÂ  and commitmentÂ  asÂ  anÂ  interveningÂ  variableÂ  ofÂ  94,13Â  %Â  andÂ  theÂ  remainingÂ  5,87Â  %Â  is explained by other variables outside our model, such as work environment, competence and others.